Degrees of "being first": toward a nuanced understanding of first-generation entrants to higher education. Issue 6 (19th September 2022) - Patfield, Sally; Gore, Jennifer; Fray, Leanne
ABSTRACT: Universities have increasingly adopted "first-generation status" as a new category for addressing equity in higher education, especially in the UK and Australia. This category targets students whose parents do not have a university degree and therefore are "newcomers" to higher education. While the category is well-intentioned, given the persistence of inequitable enrolment patterns and the need to widen participation, it has resulted in a fairly narrow and limiting view of first-generation students. Typically, students have been set in binary opposition to their peers with university-educated parents and consequently positioned within deficit discourses – as sharing a similar set of "problems" that need to be remedied by policy and practice. This paper problematises such a totalising depiction of first-generation entrants by examining diversity within the category rather than simply demarcating differences from their continuing-generation peers. Drawing on focus group data from 198 prospective first-generation students enrolled in government schools in New South Wales, Australia, we utilise the Bourdieusian lens of social capital to explore the multiple social networks within which young people are situated. We propose a new continuum that better captures how students are differentially positioned in social space, and identify three clusters based on their capacity to mobilise capital – "inheritors", "opportunists", and "outsiders". In so doing, we unsettle the symbolic boundary around what it means to "be first", and argue that this more nuanced reconceptualisation of first-generation entry is critical if the category is to be a meaningful vehicle for redressing historical exclusions and widening participation in higher education.